The importance of appropriate selection of clinical endpoints in outpatient COVID-19 clinical trials - Kristian Thorlund; Davey Smith; Christopher Linsell; Nicholas White; Christopher Butler; David Boulware; Judith Currier; Ofir Harari; Edouard Lhomme; Nathalie Strub-Wourgaft; Stacey Adam; Edward Mills (Communications Medicine, 2023)
Abstract Clinical trial endpoints must be carefully and intentionally selected so that the results of the trial can be used to inform policy- and decision-making. The relative importance of potential endpoints often depends on the stakeholder, with patients having different preferences to policymakers and regulators. The set up of clinical trials for COVID-19 was problematic, as endpoints that could be reasonably measured did not always match the efficacy endpoints usually required by guideline panels. Thus, different endpoints were used, which made the timely comparison and evaluation of interventions difficult. Here we discuss the evolution of the COVID-19 landscape and the effect this is having on the selection of consistent and measurable clinical trial endpoints. Using appropriate endpoints is crucial for researchers to offer the most reliable, valid, and interpretable results possible.